Aspectos prosódicos e textuais do gênero diálogo didático em manual de ensino de língua inglesa - Córdula, Maíra Sueco Maegava (2008)
This dissertation offers an analysis of the dialogues that open the units of study in textbooks of teaching English as a foreign language to secondary students in Brazil. The aim of this research is to learn about the representation of orality in textbooks from a sociointerationist perspective of language and by applying a linguistic approach which includes the studies of Conversation Analysis, Text Linguistics and Phonetics and Phonology of the suprasegmental elements. The investigation of the textual and prosodic features of the dialogues together with an analysis of the domains of social activity, themes and types of composition of the texts analyzed led to a characterization of the textbook dialogue gender. This has allowed some reflection on the concepts of language found in the gender studied, a notion of language as an abstract system of rules. The theoretical approach of this research does not focus on the applicability of the analysis to teaching which was the concern of the previous studies; therefore, its objective is centered on the production of this type of gender. Due to the pedagogical nature of the corpus, the results of the research can also serve as basis for future studies in Applied Linguistics. Besides that, the prosodic analysis of the audio CDs, which has not been performed before, played a significant role on the conclusions drawn in this research. Keywords: textbook dialogue; prosody; Text Linguistics; gender; concepts of language.